Risk-proportionate clinical trial monitoring: an example approach from a non-commercial trials unit - Smith, Catrin Tudur; Williamson, Paula; Jones, Ashley; Smyth, Alan R.; Hewer, Simon Langton; Gamble, Carrol (BioMed Central, 2014)
Background Some level of monitoring is usually required during a clinical trial to protect the rights and safety of trial participants and to safeguard the quality and reliability of trial results. Although there is increasing support for the use of risk-proportionate approaches to achieve these aims, the variety of methods and lack of an empirical evidence base can present challenges for clinical trial practitioners. Methods This paper describes the monitoring methods and procedures that are utilised by a noncommercial clinical trials unit which coordinates a range of clinical trials across a variety of clinical areas with different associated risks. Results Monitoring activities and approaches should be selected to be proportionate to the risks identified within a trial. A risk-proportionate approach to monitoring is described giving details of methods that may be considered by clinical trial practitioners during the development of a trial monitoring plan. An example risk assessment and corresponding monitoring plan for a low risk (type A in the Medicines and Healthcare Products Regulatory Agency (MHRA) classification system) pediatric trial is provided for illustration. Conclusion We present ideas for developing a monitoring plan for a clinical trial of an investigational medicinal product based on our experience. Alternative approaches may be relevant or preferable in other settings based on inherent risk.